In vitro Characterization of Gut Microbiota-Derived Bacterial Strains With Neuroprotective Properties - Ahmed, Suaad; Busetti, Alessandro; Fotiadou, Parthena; Vincy Jose, Nisha; Reid, Sarah; Georgieva, Marieta; Brown, Samantha; Dunbar, Hayley; Beurket-Ascencio, Gloria; Delday, Margaret I.; Ettorre, Anna; Mulder, Imke E. (Frontiers in Cellular Neuroscience, 2019)
Neurodegenerative diseases are disabling, incurable and progressive conditions characterized by neuronal loss and decreased cognitive function. Changes in gut microbiome composition have been linked to a number of neurodegenerative diseases, indicating a role for the gut-brain axis. Here, we show how specific gut-derived bacterial strains can modulate neuroinflammatory and neurodegenerative processes in vitro through the production of specific metabolites and discuss the potential therapeutic implications for neurodegenerative disorders. A panel of fifty gut bacterial strains was screened for their ability to reduce pro-inflammatory IL-6 secretion in U373 glioblastoma astrocytoma cells. Parabacteroides distasonis MRx0005 and Megasphaera massiliensis MRx0029 had the strongest capacity to reduce IL-6 secretion in vitro. Oxidative stress plays a crucial role in neuroinflammation and neurodegeneration, and both bacterial strains displayed intrinsic antioxidant capacity. While MRx0005 showed a general antioxidant activity on different brain cell lines, MRx0029 only protected differentiated SH-SY5Y neuroblastoma cells from chemically-induced oxidative stress. MRx0029 also induced a mature phenotype in undifferentiated neuroblastoma cells through upregulation of microtubule-associated protein 2. Interestingly, short-chain fatty acid analysis revealed that MRx0005 mainly produced C1-C3 fatty acids, while MRx0029 produced C4-C6 fatty acids, specifically butyric, valeric and hexanoic acid. None of the short-chain fatty acids tested protected neuroblastoma cells from chemically-induced oxidative stress. However, butyrate was able to reduce neuroinflammation in vitro, and the combination of butyrate and valerate induced neuronal maturation, albeit not to the same degree as the complex cell-free supernatant of MRx0029. This observation was confirmed by solvent extraction of cell-free supernatants, where only MRx0029 methanolic fractions containing butyrate and valerate showed an anti-inflammatory activity in U373 cells and retained the ability to differentiate neuroblastoma cells. In summary, our results suggest that the pleiotropic nature of live biotherapeutics, as opposed to isolated metabolites, could be a promising novel drug class in drug discovery for neurodegenerative disorders.